P183 Multicentre audit on the Diagnosis and Management of Trichomonas vaginalis. (30th June 2016) - Lechelt, Martin; Shen, Richard; Price, Huw; AbuBakar, Sabri; Jaleel, Henna; Ramogi, Malaki; Crowe, Gail
Abstract : Background/introduction: Trichomonas vaginalis (TV) is a sexually transmitted parasitic infection. It is commonly found in patients of non-white ethnicity and in females is usually symptomatic though may be asymptomatic in up to 50%. Untreated infection can lead to complications such as pelvic inflammatory disease, preterm delivery and increased risk of transmission of HIV. Aim(s)/objectives: To compare the management of TV in five GUM clinics across Essex to the BASHH 2014 TV guidelines Methods: Audit of 30 case notes of patients diagnosed with TV (SHHAPT code C6A) between January and December 2014 Results: Discussion/conclusion: In Essex 79% of patients diagnosed with TV were of white British ethnicity, reflecting local demographics. Nearly all were female and the majority were symptomatic. All clinics performed wet mount to diagnosed TV. It is cheap and gives an immediate result but the sensitivity is skill dependent. The regional audit group felt PCR testing should be used in the future. Written information on TV should also be improved by using approved websites and patients given BASHH leaflets.